2022
DOI: 10.3390/biomedicines10082035
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Therapeutic Targets of c-Jun-N-Terminal Kinases Activation in Nonalcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver (NAFL) is the most common chronic liver disease. Activation of mitogen-activated kinases (MAPK) cascade, which leads to c-Jun N-terminal kinase (JNK) activation occurs in the liver in response to the nutritional and metabolic stress. The aberrant activation of MAPKs, especially c-Jun-N-terminal kinases (JNKs), leads to unwanted genetic and epi-genetic modifications in addition to the metabolic stress adaptation in hepatocytes. A mechanism of sustained P-JNK activation was identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 161 publications
0
13
0
Order By: Relevance
“…Since NF-κB and AP-1 pathways regulate the expression of pro-inflammatory cytokines, these findings suggest that PPARα may exert its anti-inflammatory effects by suppressing these pathways in the liver. Previous studies reported that saturated fatty acids activate JNK in hepatocytes (50,51), whereas the hepatic JNK is required for AP-1 activation and NCOR1 expression (52). As NCOR1 is a potent co-repressor for PPARα, these findings suggest that the JNK-NCOR1 axis reciprocally affects the PPARα anti-inflammatory effect.…”
Section: Trans-acting Repressionmentioning
confidence: 77%
“…Since NF-κB and AP-1 pathways regulate the expression of pro-inflammatory cytokines, these findings suggest that PPARα may exert its anti-inflammatory effects by suppressing these pathways in the liver. Previous studies reported that saturated fatty acids activate JNK in hepatocytes (50,51), whereas the hepatic JNK is required for AP-1 activation and NCOR1 expression (52). As NCOR1 is a potent co-repressor for PPARα, these findings suggest that the JNK-NCOR1 axis reciprocally affects the PPARα anti-inflammatory effect.…”
Section: Trans-acting Repressionmentioning
confidence: 77%
“…Consequently, the heightened activation of the metabolic stress-induced MAPK cascade in hepatocytes causes significant damage to the liver. This process involves upstream MAPK kinases (MAP3K), including apoptosis signal-regulating kinase 1 (ASK1), mixed-lineage kinases (MLKs), TAK1, MAPK kinases (MAP2K) such as mitogen-activated protein kinase kinase 4 (MKK4), MKK7, and terminal stress kinases like JNK and p38 [63,64]. Moreover, serving as an inflammatory pathway associated with various chemical mediators, MAPK activation can impact other bodily systems, including the cardiovascular system.…”
Section: Biochemical and Cellular Patterns Of Mafldmentioning
confidence: 99%
“…Additionally, ASK1 is a MAP3 kinase that activates the downstream terminal kinases, JNK and p38. The ASK1 inhibitor, GS-444217, ameliorated NASH and improved fibrosis in preclinical studies and a short-term clinical trial [ 126 ]; however, this inhibitor was not effective in late-phase clinical trials [ 127 , 128 ]. Currently, biologics and the transplantation of stem cells have been shown to inhibit JNK in DILI through modulation of GSH resynthesis [ 129 ].…”
Section: Pathways For the Treatment Of A Drug-induced Liver Injurymentioning
confidence: 99%